DIAGNOSTIC IMAGING AND IONIZING RADIATION EXPOSURE IN A LEVEL 1 TRAUMA CENTRE POPULATION MET WITH TRAUMA TEAM ACTIVATION: A ONE-YEAR PATIENT RECORD AUDIT. Issue 1 (15th February 2020) - Bågenholm, Anna; Løvhaugen, Pål; Sundset, Rune; Ingebrigtsen, Tor
Abstract: This audit describes ionizing and non-ionizing diagnostic imaging at a regional trauma centre. All 144 patients (males 79.2%, median age 31 years) met with trauma team activation from 1 January 2015 to 31 December 2015 were included. We used data from electronic health records to identify all diagnostic imaging and report radiation exposure as dose area product (DAP) for conventional radiography (X-ray) and dose length product (DLP) and effective dose for CT. During hospitalization, 134 (93.1%) underwent X-ray, 122 (84.7%) CT, 92 (63.9%) focused assessment with sonography for trauma (FAST), 14 (9.7%) ultrasound (FAST excluded) and 32 (22.2%) magnetic resonance imaging. One hundred and sixteen (80.5%) underwent CT examinations during trauma admissions, and 73 of 144 (50.7%) standardized whole body CT (SWBCT). DAP values were below national reference levels. Median DLP and effective dose were 2396 mGycm and 20.42 mSv for all CT examinations, and 2461 mGycm (national diagnostic reference level 2400) and 22.29 mSv for a SWBCT.